ASSESSMENT OF THE ANTI-DIARRHEA FUNCTION OF COMPOUND CHINESE HERBAL MEDICINE CANGPO ORAL LIQUID - Xia, Xinchao; Wang, Hui; Niu, Xu; Wang, Haijun; Liu, Zhiqi; Liu, Yongming; Qi, Zhiming; Wang, Shengyi; Liu, Shixiang; Liu, Shanshan (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
To evaluate the ability of Cangpo Oral Liquid (COL), used for the inhibition of small intestine peristalsis in piglets in vitro. The preparation was fed to piglets that had diarrheal disease in order to determine its anti-diarrhea activity and potential applications in vivo. The contents of Berberine hydrochloride, Magnolol and Honokiol were performed on HPLC analysis. Organ bath was used to investigate the effect of COL on peristaltic reflexes, and peristaltic waves in vitro. And anti-diarrhea activity of COL was evaluated in clinical. Thin layer chromatography (TLC), and HPLC analyses showed that the contents of Berberine hydrochloride, Magnolol and Honokiol in COL were 970μg/mL, 130μg/mL and 300μg/mL, respectively. Administration of the COL, to the organ bath caused a concentration-dependent inhibition of intestinal peristalsis. When the COL concentration in the bath was cumulatively increased; the amplitude and frequency of the peristaltic waves was lowered. The result of clinical efficacy of COL was very effective to diarrheic piglets. COL can possibly inhibit the curve of peristaltic waves in vitro; and clinical trial showed a statistically significant therapeutic effect in vivo. COL can be used as an effective therapeutic agent. However, the ingredients, pharmacokinetics and specific signaling pathways of COL need to be further studied.